Describing Students’ Activeness in Distance Learning During Covid-19 Pandemic Time - Nenik Molebu (Sintuwu Maroso Journal of English Teaching, 2021)
The objective of the research is to describe the level of students’ activeness in learning during Covid 19 Pandemic time at SMP Negeri 3 Poso Kota Utara. The type of the research was qualitative research. The subject of the research were Eight grade students of SMP Negeri 3 Poso Kota Utara, consist of 25 students. Data collection technique used were documentation, interviews and questionnaire. The technique of data analyzed using the excel program. Based on the research of the study, the level of students activities was classified as active. The percentage of students’ activeness is (68,44%) or in the level is active. The kinds of students’ activeness were visually active (12,4%) the students paid attention to the teacher's explanation of the material that had been sent. Orally active (9,08%) that the students answered the question given by the teacher. Listening active (4,52%) that the students can make example and listen carefully when the teacher teach them. Writing active (8%) that the students not the important things. Drawing active (4,92) that the students give their opinion when the teacher ask. Motorically active (11%) that the students can do by themself when opening the material with a laptop or smartphone, can send assignments by them self via smartphone or laptop and try to find supporting material myself to learn from YouTube. Mentally active (13,28%) that the student try to complete the assignment given by the teacher according to the set time. Emotionally active (6,28% )that they are interested in the material that the teacher sends